Bound for murder - Gilbert, Victoria (Gilbert, Victoria. Blue Ridge library mystery., 2020)
Taylorsford Public Library director Amy Webber's friend "Sunny" Fields is running for mayor. But nothing puts a damper on a campaign like an actual skeleton in a candidate's closet. Sunny's grandparents ran a commune back in the 1960s on their organic farm. But these former hippies face criminal charges when human remains are found in their fields--and a forensic examination reveals that the death was neither natural nor accidental. With Sunny's mayoral hopes fading, Amy sets her wedding plans aside, says "not yet" to the dress, and uses her research skills to clear her best friend's family. Any of the now-elderly commune members could have been the culprit. As former hippies perish one by one, Amy and her friends Richard, Aunt Lydia, and Hugh Chen pursue every lead. But if Amy can't find whoever killed these "flower children," someone may soon be placing flowers on her grave.